The dual use of mass media in Chinese popular diplomacy to achieve economic dominance in Africa: Conference on Cultural Diversity, the Basis of National Integration, College of Arts/Wasit University 2022 - Mustafa Hussein Abdulrazq, Ass.Prof. Dr. (lark, 2022)
China has practiced people’s diplomacy or (citizen diplomacy) in Africa by spreading its culture through Confucius Institutes, organizing employment fairs, as well as preparing and implementing education and training programs for the development of African human resources. China used the media to appeal to the Chinese public to encourage it to participate in the practices of popular diplomacy, and the success in this approach was demonstrated by comparing the opinions of the public at different times,On the other hand, the Chinese media directed the African audience. China has established branches for Chinese media, news agencies and broadcasts, and these media have focused on a number of contents, including historical links, success stories, abundance of opportunities in Africa, Chinese generosity in Africa, the great importance of Africa, China’s pursuit of partnership, not hegemony, and that the Chinese model of development is more suitable for Africa, and as a result, China has achieved its desired economic hegemony at various levels (trade, investment, and debt).